(untitled) (Altre Modernità, 2018)
Given the prominence of initiating and maintaining the discussion of the controversial issues in the second language (L2) classrooms and settings and its probable effects on teacher credibility, the present study intends to explore the relationship between envolvement of the students in the controversial issues and teacher credibility in light of the emotioncy hierarchies (avolvement, exvolvement, and involvement). To this end, a total of 228 undergraduate students of English were asked to take the envolvement of the controversial issues scale (ECIS) along with the teacher credibility questionnaire. Confirmatory factor analysis (CFA) was used to substantiate the construct validity of the ECIS. Subsequently, structural equation modeling (SEM) was employed to examine whether the sub-constructs of the ECIS have any possible relationships with teacher credibility. The findings demonstrated that students’ avolvement with regard to the controversial issues could bring about teacher credibility, while exvolvement and involvement bear no significant relationship with teacher credibility. Finally, the pedagogical implications of the findings are discussed and some suggestions are made for the future studies within the realm of L2 education and the classroom discussions.